2021
DOI: 10.3390/pharmaceutics13071005
|View full text |Cite
|
Sign up to set email alerts
|

Development of Dual ARV-825 and Nintedanib-Loaded PEGylated Nano-Liposomes for Synergistic Efficacy in Vemurafnib-Resistant Melanoma

Abstract: A novel treatment strategy by co-targeting c-Myc and tumor stroma was explored in vemurafenib-resistant melanoma. BRD4 proteolysis targeting chimera (ARV-825) and nintedanib co-loaded PEGylated nanoliposomes (ARNIPL) were developed to incorporate a synergistic cytotoxic ratio. Both the molecules have extremely poor aqueous solubility. A modified hydration method with citric acid was used to improve the loading of both the molecules in liposomes. ARNIPL with mean particle size 111.1 ± 6.55 nm exhibited more tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…In antiretroviral drug-loaded PEG-polylactic-co-glycolic acid polymer nanoparticles in pancreatic cancer two-dimensional cell culture and three-dimensional multicellular tumor spheroids, the model can continue to explain that BRD4 shows a good anticancer effect and can effectively treat pancreatic cancer [ 46 ]. Experimental results have also shown excellent synergistic effects of dual ARV-825 and nintedanib-loaded PEGylated nanoliposomes in melanoma, providing a new approach for the treatment of vemurafenib-resistant melanoma [ 47 ]. Experiments with ARV-825-loaded nanoliposomes in lung cancer and hepatocellular carcinoma have shown that nano-fusion leads to better tumor penetration and lethality [ 48 , 49 ].…”
Section: Protacs For Epigenetic Targets In Cancermentioning
confidence: 99%
“…In antiretroviral drug-loaded PEG-polylactic-co-glycolic acid polymer nanoparticles in pancreatic cancer two-dimensional cell culture and three-dimensional multicellular tumor spheroids, the model can continue to explain that BRD4 shows a good anticancer effect and can effectively treat pancreatic cancer [ 46 ]. Experimental results have also shown excellent synergistic effects of dual ARV-825 and nintedanib-loaded PEGylated nanoliposomes in melanoma, providing a new approach for the treatment of vemurafenib-resistant melanoma [ 47 ]. Experiments with ARV-825-loaded nanoliposomes in lung cancer and hepatocellular carcinoma have shown that nano-fusion leads to better tumor penetration and lethality [ 48 , 49 ].…”
Section: Protacs For Epigenetic Targets In Cancermentioning
confidence: 99%
“…Researchers have been trying to develop novel drug delivery systems to improve the site-specific targeting of the bioactive compounds along with their enhanced efficacy. The use of nanotechnology and thus nanoformulations has been extensively explored [ 256 , 257 , 258 , 259 ]. Below are a few examples of novel drug delivery methods to enhance the efficacy of phytocompounds.…”
Section: Novel Strategies For Enhanced Delivery Of Natural Food Bioac...mentioning
confidence: 99%
“…Remarkably, several recent studies on melanoma treatment have demonstrated that the efficacy of MAPK‐targeting therapies, [16,17] and immunotherapies [18] are significantly improved by the co‐administration of nintedanib, thus emphasizing the role of this small molecule in TME normalization.…”
Section: Introductionmentioning
confidence: 99%
“…[14] Nintedanib, a small-molecule tyrosine kinase inhibitor, clinically approved as an antifibrotic drug, inhibits the accumulation and activation of fibroblasts so too their transition into myofibroblasts, as well as the deposition of the ECM. [15] Remarkably, several recent studies on melanoma treatment have demonstrated that the efficacy of MAPK-targeting therapies, [16,17] and immunotherapies [18] are significantly improved by the co-administration of nintedanib, thus emphasizing the role of this small molecule in TME normalization.…”
Section: Introductionmentioning
confidence: 99%